Language Ideology and Power in Educational Policy Discourse: A Critical Sociolinguistic Analysis - Aisyah Nur Aina Abdullah (Pemuda Peduli Publikasi Insan Ilmiah, 2026)
Purpose: This study aims to critically examine how language ideology and power are constructed, negotiated, and institutionalized within educational policy discourse in multilingual contexts. It seeks to uncover how policy texts and institutional narratives shape linguistic hierarchies, marginalize minority languages, and legitimize particular language choices as natural or inevitable. Subjects and Methods: The research adopts a qualitative critical sociolinguistic design grounded in Critical Discourse Analysis (CDA). Data consist of thirty-six national and regional educational policy documents from Asia, Europe, and Africa, complemented by semi-structured interviews with policymakers and senior educators. Analytical procedures included thematic coding, discursive and lexical analysis, and triangulation between policy texts and interview data to identify dominant ideologies and power relations embedded in language policy discourse. Results: The findings reveal a consistent prioritization of national and global languages particularly English as legitimate carriers of academic knowledge and economic value, while minority and heritage languages are symbolically acknowledged but functionally constrained. Policy discourse reflects strong neoliberal rationalities, framing language as economic capital linked to competitiveness and employability. Multilingual learners are often problematized through deficit-oriented representations, and minority language communities are largely excluded from decision-making processes, reinforcing top-down governance and linguistic inequality. Conclusions: Educational policy discourse functions as a powerful ideological mechanism that normalizes linguistic hierarchies and marginalizes minority language agency. Addressing these dynamics requires participatory, equity-oriented language policies that recognize multilingualism as a central resource for sociolinguistic justice and educational inclusion.